ANALYSIS OF THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER LOYALTY WITH MEDIATED CUSTOMER SATISFACTION IN IMPROVING BUSINESS PERFORMANCE AT WELERI FRESH COW MILK DEPOT - Andy Kurniawan, Andy Kurniawan; Dorojatun Prihandono (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the effect of product quality and service quality on consumer loyalty mediated by consumer satisfaction in improving business performance at Weleri Fresh Cow Milk Depot. The population in this study were consumers of Weleri Fresh Cow Milk Depot. The sampling technique uses simple probability sampling. The sample in this study numbered 100 consumers of Weleri Fresh Cow Milk Depot. In this study using four variables, namely service quality, product quality, customer loyalty and customer satisfaction. The results of this study indicate that Product Quality has a partially significant positive effect on Customer Loyalty, Product Quality has a partially significant positive effect on Consumer Satisfaction, Service Quality has a partially significant positive effect on Consumer Loyalty, Service Quality has a partially significant positive effect on Consumer Satisfaction, Satisfaction Consumers have a partially significant positive effect on Consumer Loyalty, Product Quality mediated by Consumer Satisfaction has a significant positive effect on Consumer Loyalty, Service Quality mediated by Consumer Satisfaction has no significant positive effect on Consumer Loyalty. Suggestions for the existing weleri fresh cow’s milk can maintain brand variance and price stability in accordance with consumer desires.